2015
DOI: 10.1590/0004-282x20150066
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative changes in the brainstem and olfactory bulb in people older than 50 years old: a descriptive study

Abstract: With the increase in life expectancy in Brazil, concerns have grown about the most prevalent diseases in elderly people. Among these diseases are neurodegenerative diseases, such as Alzheimer’s and Parkinson’s diseases. Protein deposits related to the development of these diseases can pre-date the symptomatic phases by years. The tau protein is particularly interesting: it might be found in the brainstem and olfactory bulb long before it reaches the limbic cortex, at which point symptoms occur. Of the 14 brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Numerous studies have found amyloid and tau deposition in the olfactory bulbs of humans at autopsy and in AD animal models [15] , [16] , [20] , [22] , [23] , [24] , [27] , [28] . PET does not offer sufficient resolution for measurement of amyloid and/or tau deposition in the olfactory bulb in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have found amyloid and tau deposition in the olfactory bulbs of humans at autopsy and in AD animal models [15] , [16] , [20] , [22] , [23] , [24] , [27] , [28] . PET does not offer sufficient resolution for measurement of amyloid and/or tau deposition in the olfactory bulb in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The precise biological correlates of the observed changes in olfactory identification have not been specifically identified. However, previous studies have sought to determine the impact of the two major pathophysiological hallmarks of AD, amyloid β plaques and tau neurofibrillary tangles, on olfaction in animal models of AD [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , autopsy studies [23] , [24] , [25] , [26] , [27] , [28] , [29] , and more recently in living human beings using imaging biomarkers of amyloid pathology, measured using neuroimaging with positron emission tomography (PET) techniques [30] , [31] , [32] . Animal models of AD show considerable olfactory deficits that are related to the deposition of amyloid and tau in the olfactory bulb and throughout the olfactory network [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [33] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deposition of tau and b-amyloid in the olfactory bulb in the earliest stages of Alzheimer disease is well documented. 93,94 Olfactory impairment in Parkinson disease also is described. 95 Examination of olfactory mucosal neurons from nasal brushings provides for a diagnostic test in living patients.…”
Section: Olfactory Involvement In Other Disordersmentioning
confidence: 99%
“…For developmental neuroscientists, consideration of regressive changes that occur at the other extreme of the age spectrum often provide clues to mechanisms of ontogenesis, in both the human and rodent models. 94,[110][111][112] After age 50 years, most individuals experience gradual loss of olfactory discrimination, hyposmia, or even total anosmia in the elderly, after controlling for dementia and medical comorbidity. 111 There are several explanations for this change, not due to neurodegenerative disease.…”
Section: Olfaction In Ageingmentioning
confidence: 99%